UTILISING GROUP WORK IN THE IMPLEMENTATION OF FAMILY PRESERVATION SERVICES: VIEWS OF CHILD PROTECTION SOCIAL WORKERS - Van Huyssteen, Josane; Strydom, Marianne (Social Work/Maatskaplike Werk, 2016)
The largest area of service rendering in social work in South Africa pertains to child and family welfare. Policy directives indicate that services should be aimed at reducing child abuse and neglect while protecting the child and preserving the family unit. Group work is a cost-effective intervention strategy to be implemented to meet the high demand for child protection services. However, social workers face various challenges when utilising group work in service delivery. Yet because of the advantages of group work in addressing the social isolation of at-risk families, this intervention method should be incorporated into family preservation programmes.